2021
DOI: 10.47108/jidhealth.vol4.issspecial1.103
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice regarding COVID-19 pandemic among medical students of Ernakulam, India

Abstract: Background: COVID – 19 infection is a serious pandemic the world is now facing. This study aimed to assess the knowledge, attitude, and practice regarding COVID-19 infection among medical students at a private medical college in central Kerala.  Methods: A cross-sectional web-based study was conducted during April-May 2020 in a private medical college in Ernakulam District using the Universal sampling technique. The study tool was a semi-structured validated questionnaire containing sociodemographic deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The results of our study coincide with the results of previous studies conducted by Galasso et al [30] and de la Vega et al [31], which confirmed that women take the COVID-19 pandemic more seriously and adhere to the standards of protection from the coronavirus more than men. In line with previous studies [14,16,32], regression analysis showed that married (P=0.038) and those who have experience of 10 years and above (P=0.038) showed an optimistic attitude towards the COVID-19 pandemic. Moreover, senior health professionals have acquired the skills and knowledge to act wisely when dealing with health crises such as the COVID-19 pandemic [33].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of our study coincide with the results of previous studies conducted by Galasso et al [30] and de la Vega et al [31], which confirmed that women take the COVID-19 pandemic more seriously and adhere to the standards of protection from the coronavirus more than men. In line with previous studies [14,16,32], regression analysis showed that married (P=0.038) and those who have experience of 10 years and above (P=0.038) showed an optimistic attitude towards the COVID-19 pandemic. Moreover, senior health professionals have acquired the skills and knowledge to act wisely when dealing with health crises such as the COVID-19 pandemic [33].…”
Section: Discussionsupporting
confidence: 90%
“…In the linear regression analysis, women showed a more positive attitude (P=0.022) toward COVID-19 than men. Several previous studies [14][15][16][27][28][29][30][31] reported higher morbidity and mortality rates among men than women. Peckham et al [28] found that the likelihood of needing an intensive therapy unit is approximately three times higher for men than for women.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Yakar et al 13 16 found that the average score in the knowledge questionnaire was 9.8 (S.D.=1.62, range=0-12). Another study by Kalliath et al 17 studied the knowledge, attitude, and practices regarding COVID-19 pandemic among medical students of Ernakulam, India. They found that most medical students had sufficient knowledge (81.6%) and attitudes (91.3%) on the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%